2018
DOI: 10.1007/978-3-030-04792-4_6
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Various Approaches to Reinforcement Learning Algorithms for Multi-robot Box Pushing

Abstract: In this paper, a comparison of reinforcement learning algorithms and their performance on a robot box pushing task is provided. The robot box pushing problem is structured as both a singleagent problem and also a multi-agent problem. A Q-learning algorithm is applied to the single-agent box pushing problem, and three different Q-learning algorithms are applied to the multi-agent box pushing problem. Both sets of algorithms are applied on a dynamic environment that is comprised of static objects, a static goal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…The region-growing curriculum is also applied for multi-robot object transportation (lines 6-7). Using the Q single -network with a probability of ψ, each robot can take approaching and transport actions from the beginning (lines [12][13][14][15]. With the help of the actions by Q single -network, multiple robots can train their network Q multi (lines [16][17][18][19][20].…”
Section: Single-to Multi-robot Curriculummentioning
confidence: 99%
See 2 more Smart Citations
“…The region-growing curriculum is also applied for multi-robot object transportation (lines 6-7). Using the Q single -network with a probability of ψ, each robot can take approaching and transport actions from the beginning (lines [12][13][14][15]. With the help of the actions by Q single -network, multiple robots can train their network Q multi (lines [16][17][18][19][20].…”
Section: Single-to Multi-robot Curriculummentioning
confidence: 99%
“…They showed that the performance of single-agent Q-learning was better than that of team Q-learning due to the lack of sufficient random actions. Rahimi et al [ 13 ] compared single and multi-robot cases with RL-based approaches. They showed that the performance of cooperative box-pushing could be improved by frequent Q-table updates.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-sensor data retrieval for cloud robotic systems is a multiple, cooperative, real-time task (Wang et al, 2015). Multiple mobile robots push boxes together, which is a single, cooperative, real-time task (Rahimi et al, 2019). For the multiagent warehouse system, the task is single, individual, realtime.…”
Section: Multi-agent Task Allocationmentioning
confidence: 99%
“…23,24 Reinforcement learning has been implemented cooperatively in a variety of ways for multiagent environments, such as a GridWorld 25,26 and box pushing. 27 Although all of these use for consensus, movement control, and reinforcement learning that are good in their own right, this article aims to make a more intelligent hybrid system.…”
Section: Introduction Motivationmentioning
confidence: 99%